Burning of Eichhornia Sp. Versus Wetlands Biodiversity: A Case Study in Bichia Block, Unaao District, Uttar Pradesh - Kumar, Adesh; Kanaujia, Amita (Indian Forester, 2017)
The Global Fire Partnership (GFP) is working on positive and negative impacts of fire and control measures. The GFP is working on positive and negative impacts of fire and control measures. Fire plays a key role in shaping our environment and maintaining biodiversity. But fire also have negative impact on biodiversity and alter the hydrology of a site, and present a direct risk to biodiversity and human habitation. The present study is aimed to access the negative impact and loss of biodiversity due to the unregulated and uncontrolled fire to control weed (Eichhornia sp.) in Bakrain Jheel during rainy season. Study is done in Bakrain Jheel, Purwa Oonchgaaon, Bichia Block, Unnao in the month of June 2015. People lit the fire in wetlands to avoid the threats of wild animals and robbers. The study concluded that due to fire, a catastrophic loss of wetlands flora and fauna recorded from the study site. A disastrous loss of faunal biodiversity especially large number of insects, annelids, molluscks and reptiles approximately 110 pond turtle of (Actinemys marmorata) were found dead. Lot of studies should be done and defined protocol and guideline shouldbe let down for the stakeholders (fisheries stakeholders, chestnut culture stakeholders and water chest nut stakeholders) and for villagers.